Adsorption of Cr (VI) ion from tannery wastewater on tea waste: Kinetics, equilibrium and thermodynamics studies. Issue 3 (June 2019) - Nigam, Mohit; Rajoriya, Sunil; Rani Singh, Shraddha; Kumar, Pradeep
Highlights: Tannery wastewater was treated using an unconventional adsorbent. Effects of various process parameters on adsorption of Cr(VI) were examined. Adsorbent showed good performance in Cr(VI) removal from tannery wastewater. Reusability test of the adsorbent was investigated. Abstract: The present work dealt with the ability of an unconventional adsorbent to remove hexavalent chromium (Cr (VI)) from real tannery wastewater in a batch system. The low-cost and highly efficient adsorbent was prepared from tea waste (TW). The characterization of adsorbent was done by thermo-gravimetric analysis (TGA), BET surface area analysis, Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM) with energy dispersive x-ray spectroscopy (EDS). Key parameters including adsorbent dosages, solution pH, contact time, temperature and effluent concentration on the adsorption process were optimized for the best removal efficiency of Cr (VI). It was found that solution pH played an important role in removing the chromium. Almost 97% removal of Cr (VI) was achieved under the optimized conditions (viz. adsorbent dosages of 6 g/L, solution pH of 3.9, contact time of 240 min and temperature of 303 K). The % removal of Cr (VI) increased with dilution of the samples. The adsorption data followed the pseudo-second order kinetics model, and the corresponding rate constant was observed as 2.12 × 10 −4 g mg -1 min -1 with a high value of regression coefficient (R 2 = 0.9901). Langmuir isotherm model provided the best fit for Cr (VI) adsorption than other isotherms. Thermodynamic study demonstrated the endothermic nature of the adsorption process. At the optimum conditions, adsorption process with TW as an adsorbent also caused removal of 74.8% COD, 55% TDS and 71% TS from tannery effluent. Reusability tests exhibited the confirmation about stability of adsorbent and slight fluctuation in adsorbent efficiency when used upto five runs.